DIAGNÓSTICO DE LA SEGURIDAD CIUDADANA EN LA PARROQUIA VILCABAMBA DE LA PROVINCIA DE LOJA DURANTE EL PERIODO 2018 - COLLAHUAZO QUIZHPE, JOSÉ LUIS (2019)
The purpose of this thesis is to make a diagnosis of citizen security in the Vilcabamba parish of the province of Loja during the 2018 period, it was carried out in compliance with the guidelines for the presentation of the Final Thesis Report of the Public Administration Degree, considering each phase of the research process, based on the synthetic deductive and analytical methods applied to its scope of action. For the fulfillment of the following objectives the field instruments were elaborated, such as the survey, carried out on men and women with an age range that ranges from 15 to 64 years, giving a population of 345 people, and the interview with the different authorities of the Cantonal Council of Citizen Security of the Province of Loja. The purpose of the investigation is to determine the causes and participation of citizens in the face of citizen insecurity, in this way the factors, the control mechanisms were determined and the actions carried out by the control bodies regarding citizen security were identified, From the data obtained by the field instruments, it was passed to the results and then to the discussion where the results were compared, contrasted and discussed, and then give way to the conclusions and recommendations.